2020
DOI: 10.1111/pce.13814
|View full text |Cite
|
Sign up to set email alerts
|

Root isoprene formation alters lateral root development

Abstract: Isoprene is a C5 volatile organic compound, which can protect aboveground plant tissue from abiotic stress such as short-term high temperatures and accumulation of reactive oxygen species (ROS). Here, we uncover new roles for isoprene in the plant belowground tissues. By analysing Populus x canescens isoprene synthase (PcISPS) promoter reporter plants, we discovered PcISPS promoter activity in certain regions of the roots including the vascular tissue, the differentiation zone and the root cap. Treatment of ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 86 publications
(179 reference statements)
2
16
0
Order By: Relevance
“…The VOCs that are produced by roots can be similar to those produced by other organs or they can be organ specific. For example, isoprene, a major plant VOC typically formed in leaves of poplar, is also produced by roots albeit at much lower rates than in leaves [59]. In tomato, [34] analyzed the terpene profiles of different tissues and reported relatively high amounts of geraniol and β-phellandrene in roots, which coincides with the terpenes are that present in our root extracts.…”
Section: Belowground Emissionssupporting
confidence: 61%
“…The VOCs that are produced by roots can be similar to those produced by other organs or they can be organ specific. For example, isoprene, a major plant VOC typically formed in leaves of poplar, is also produced by roots albeit at much lower rates than in leaves [59]. In tomato, [34] analyzed the terpene profiles of different tissues and reported relatively high amounts of geraniol and β-phellandrene in roots, which coincides with the terpenes are that present in our root extracts.…”
Section: Belowground Emissionssupporting
confidence: 61%
“…Because microbes often grow in close association with plants, the signalling distance may be shorter than in the plant–plant interactions described here. Recently, it has been shown that root‐internal isoprene can lead to changes in root architecture and redox status in certain root cells (Miloradovic van Doorn et al, 2020). For example, if epiphytic or endophytic bacteria release isoprene, the compound could lead to sensitive adjustments in plant redox balance and alter plant performance.…”
Section: Discussionmentioning
confidence: 99%
“…With the current knowledge, it seems difficult to exclusively consider isoprene as a stress signaling molecule, since various reports relate isoprene to plant growth and development. Recent results obtained in both poplar and Arabidopsis plants have shown that IspS gene promoter activity takes place in many plant parts, including different root regions such as vascular tissue, root hairs, root cap and developing lateral roots [ 65 ]. Promoter activity was stimulated by the treatment with the growth hormone indole-3-acetic acid, and transgenic poplar plants unable to emit isoprene showed increased formation of lateral roots [ 65 ].…”
Section: Isoprene As Hormone Regulating Plant Antioxidant System and Growthmentioning
confidence: 99%
“…Recent results obtained in both poplar and Arabidopsis plants have shown that IspS gene promoter activity takes place in many plant parts, including different root regions such as vascular tissue, root hairs, root cap and developing lateral roots [ 65 ]. Promoter activity was stimulated by the treatment with the growth hormone indole-3-acetic acid, and transgenic poplar plants unable to emit isoprene showed increased formation of lateral roots [ 65 ]. Isoprene-emitting Arabidopsis plants transformed with the IspS gene from Eucalyptus globulus showed increased hypocotyl, cotyledon, leaf and inflorescence growth, suggesting that isoprene may exert its effects on growth through direct regulation of gene expression [ 51 ].…”
Section: Isoprene As Hormone Regulating Plant Antioxidant System and Growthmentioning
confidence: 99%